Practices and knowledge in phytotherapy among health professionals in Basic Health Units in the City of Campina Grande, PB (Research, Society and Development, 2021)
Objective: To know the practices and knowledge, in phytotherapy, of health professionals from Basic Health Units (UBS), in the city of Campina Grande, Paraiba. Methodology: Cross-sectional, exploratory and descriptive study, carried out using an appropriate questionnaire. After the descriptive statistical analysis, some correlations between variables were analyzed using the chi-square test and Fischer's exact test, with a significance level of 5%. Results and Discussion: Among the professionals (n = 93) just over half (50.6%) reported having acquired knowledge about herbal medicine on their own initiative. Only 25.8% of these professionals prescribed or advised the use of medicinal plants for patients. In all of these cases, the relationship between the plant species mentioned and the indicated use was supported by the scientific literature; despite this, only 30 (32.3%) answered that they feel qualified to prescribe / guide the use of medicinal plants and herbal medicines. Respondents (98.9%) agree with the implementation of a herbal medicine program in the municipal health system. As statistically significant correlations, we had that among professionals who have an adequate concept about herbal medicine, women predominate (p = 0.027), and that graduated professionals prescribe or guide the use of medicinal plants and herbal medicines, more than non-graduated professionals (p = 0.047). Conclusion: The prescription and / or guidance for the use of medicinal plants and / or phytotherapics is not a reality among most of the interviewees, requiring investments in the training of these health professionals, in order to promote rational phytotherapy in Primary Health Care.